Globalization - McMichael, Phillip (The Handbook of Political Sociology states, civil societies, and globalization, 2005)
Philip McMichael casts a critical eye on the process of globalization suggesting that it takes different forms across time and space. He specifies contemporary globalization as a discursive project, geared to institutionalizing corporate markets through multilateral and regional economic agreements driven by powerful states. From this perspective of depicting globalization as an exercise in power, he examines political countermovements to globalization. Global justice movements, he argues, are globalization’s “historical and relational barometer,” and they operate at various, but often interrelated, scales. Work- ing from Karl Polanyi’s “double movement” of implementation of and resistance to economic liberalism, McMichael questions the adequacy of Polanyi’s formulation for the elaboration of market rule in the twenty-first century. This question concerns the conventional interpretation of “sovereignty” as the centerpiece of nation-state formation, including the development of citizenship. Here, globalization is viewed through the lens of a sovereignty crisis, where corporate market rule compromises the social contract upon which the state/citizen relation is founded. The crisis is expressed differently across the world, as the impact of market rule generates alternative social movement conceptions of sovereignty, especially in the global south where corporate globalization is realized through a drastic intensification of social exclusion.
Sociology
Keywords: counter-movement; critique; double movement; globalization; political sociology

Karl Polanyi as a Development Economist - Polanyi Levitt, Kari (Pioneers of Development Economics: Great Economists on Development, 2005)
The history of modern economic thought has been pre-occupied with the question of economic transformation or development. This survey of important contributions to the economics of development includes many economists not normally considered as pioneers in this field. The contributors point to the role of imperialist considerations in the early development of economic thought and the development discourse, and the impact of pressures for social and political reform. The economists and thinkers discussed include William Petty, David Ricardo, Friedrich List, Alexander Hamilton, Karl Marx, Vladimir Ilyich Lenin, Alfred Marshall, Michal Kalecki, John Maynard Keynes, Nicholas Kaldor, Karl Polanyi, Raul Prebisch, Arthur Lewis, Alexander Gerschenkeron and Hans Singe
Economics
Keywords: development economics; economic history

Social Embeddedness. Within Political Economy: The Work of Karl Polanyi - Watson, Matthew (Foundations of International Political Economy, 2005)
BOOK ABSTRACT: Despite a burgeoning debate on substantive issues in IPE, little attention has been devoted to its theoretical foundations. In this important new text, Matthew Watson reviews the main current theoretical approaches to IPE and highlights the problems that arise from treating 'states' and 'markets' as separate and contesting units of analysis. Foremost among these problems is the lack of attention given to theorizing the constitution of the individual as both an economic agent and a moral being.
Political Science
Keywords: international political economy; social embeddedness